IMPLEMENTASI MANAJEMEN MUTU TERPADU DI PONDOK PESANTREN AL-FALAH SUMENEP - Abdul Azis (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2022)
Islamic boarding schools are educational institutions that have been recognized through law No. 20 of 2003 and also have an obligation to contribute to achieving national education goals. This study aims to describe the implementation of integrated quality management in Al-Falah Islamic Boarding School Sumenep by using a qualitative approach as well as interviews, observations, and documentation as data collection techniques. The results showed that the main vision of the Al-Falah Sumenep Islamic Boarding School is to produce community leaders (mundirul-qoum) with five souls, namely the soul of sincerity, independence, simplicity, ukhuwah Islamiyah, and the spirit of freedom. All activities are designed for the benefit of students as the main input (raw input) in education. learning at the Al-Falah Islamic boarding school Sumenep is designed with a 24-hour learning model, while curricular learning is carried out classically. Teachers or teachers at the Al-Falah Sumenep Islamic Boarding School were recruited from Al-Falah Sumenep alumni themselves with several criteria, namely scientific competence, teaching competence, and personality. A thorough evaluation was carried out on Thursday and led directly by the leadership of the Al-Falah Sumenep Islamic boarding school followed by all teachers to ensure that the activities and activities of the pesantren went according to plan.